Pattern recognition : 40th German Conference, GCPR 2018, Stuttgart, Germany, October 9-12, 2018, Proceedings /: 40th German Conference, GCPR 2018, Stuttgart, Germany, October 9-12, 2018, Proceedings. (2019) - Unknown
No abstract available